2012
DOI: 10.1261/rna.028308.111
|View full text |Cite
|
Sign up to set email alerts
|

Stability of single-nucleotide bulge loops embedded in a GAAA RNA hairpin stem

Abstract: Forty-six RNA hairpins containing combinations of 39 or 59 bulge loops and a 39 or 59 fluorescein label were optically melted in 1 M NaCl, and the thermodynamic parameters DH°, DS°, DG°3 7 , and T M for each hairpin were determined. The bulge loops were of the group I variety, in which the identity of the bulge is known, and the group II variety, in which the bulged nucleotide is identical to one of its nearest neighbors, leading to ambiguity as to the exact position of the bulge. The fluorescein label at eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 33 publications
4
11
0
Order By: Relevance
“…Some of the hairpins in Table 5 have a fluorescein tag at either the 5 ′ or 3 ′ end. We have previously shown that the fluorescein tag does not affect the thermodynamics of hairpin formation (Lim et al 2012), so we will not consider it further in our analysis. Again, there is a multitude of ways to analyze the influence of a group III bulge on the thermodynamics of hairpin formation due to the ambiguity of the bulged nucleotide.…”
Section: Structural Determination Of the Group III Bulged Nucleotide mentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the hairpins in Table 5 have a fluorescein tag at either the 5 ′ or 3 ′ end. We have previously shown that the fluorescein tag does not affect the thermodynamics of hairpin formation (Lim et al 2012), so we will not consider it further in our analysis. Again, there is a multitude of ways to analyze the influence of a group III bulge on the thermodynamics of hairpin formation due to the ambiguity of the bulged nucleotide.…”
Section: Structural Determination Of the Group III Bulged Nucleotide mentioning
confidence: 99%
“…The in-line probing results show that the bulged nucleotide was the one further from the hairpin loop, so we selected this nucleotide as the bulge, irrespective of whether or not this led to the formation of a wobble base pair. For group II bulge loops imbedded in a hairpin stem, the stability of the hairpin stem distal from the hairpin loop gave the best prediction of the influence of the bulge on the thermodynamics of hairpin formation (Lim et al 2012). Therefore, we chose a similar model, using the stability of the distal stem and Equation 5, to predict the influence of the group III bulge loops on hairpin stability.…”
Section: Structural Determination Of the Group III Bulged Nucleotide mentioning
confidence: 99%
See 1 more Smart Citation
“…The substitution of 2-AP in either the proximal (base-paired, stacked) or distal (bulged, not stacked) position of the group II bulges leads to nearly the same change in thermodynamic stability of the hairpins (Table 2); therefore, it is not possible to relate the structure of the Lim et al (2012). d Kent et al (2014).…”
Section: Modulation Of 2-ap Fluorescence By Thermal Denaturation Of Rmentioning
confidence: 99%
“…The current work is a continuation of our studies on the stability and structure of bulge loops in the context of an RNA hairpin stem (Lim et al 2012;Kent et al 2014). A simple model has been proposed to predict the influence of bulge loops on the stability of hairpin formation that depends upon non-nearest-neighbor interactions (stability of the stem distal to the hairpin loop) (Kent et al 2014).…”
Section: Introductionmentioning
confidence: 96%